2017
DOI: 10.15207/jkcs.2017.8.4.079
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Relationships among Appearance Satisfaction, Self-Esteem, and Problem-Solving Ability of Adolescent

Abstract: This study was a descriptive survey grasping the convergent relationship among the appearance satisfaction, self-esteem, and problem-solving ability of adolescents. The participants were 158 students of two middle schools in J city. The appearance satisfaction, self-esteem, problem-solving ability and general characteristics of students were measured. The data were collected from September 26 to October 14, 2016. The collected data was analyzed with t-test, ANOVA, Pearson's correlation coefficients.As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
0
0
1
Order By: Relevance
“…We found there were differences in appearance concerns between male and female, and this accorded with what Cho [18], Jang and Kang [26], Polce-Lynch et al [27], Shim [28] and others had reported. In addition, not only do female students have more appearance concerns compared to males but they experience the concerns earlier in life than males.…”
Section: Resultssupporting
confidence: 92%
“…We found there were differences in appearance concerns between male and female, and this accorded with what Cho [18], Jang and Kang [26], Polce-Lynch et al [27], Shim [28] and others had reported. In addition, not only do female students have more appearance concerns compared to males but they experience the concerns earlier in life than males.…”
Section: Resultssupporting
confidence: 92%
“…Another important finding is that self-esteem is the factor that has the greatest influence on this research. This finding is in line with the research results by Koruklu (2015) and Jang and Kang (2017), which also place self-esteem as a factor that has a powerful influence in influencing social problem-solving. Individuals with positive self-esteem believe that they are valuable people, view stress more positively, and can solve various problems in their lives (Hall, Crutchfield, & Jones, 2018).…”
Section: Resultssupporting
confidence: 91%
“…헤어스타일은 현대인의 첫인상을 긍정적이거나 부정적으로 평가하는 잣대로 작용하기도 하며, 이미지를 아름답게 변신하고자 할 때 커다란 영향을 준다. 이러한 헤어스타일은 인상, 인격, 성격, 가치관뿐만 아니라 당대(當代) 문화를 대변시켜 주는 도구로 작용하기 때문에 현대사회에서 매우 중요한 수단이다 [9]. 더불어 모발을 단순히 다듬거나 꾸미는 일반적인 시술 범위를 초월하여 모발에 물리적, 화학적인 시술을 거치면서 현대인의 외적 이미지를 아름답게 표출하는 수단이기도 하다 [10].…”
Section: 서론 광속(光速)으로 급변하는 4차 산업혁명 시대를 사는 현대인은 과학기술의 눈부신unclassified